2016
DOI: 10.1002/chem.201504161
|View full text |Cite
|
Sign up to set email alerts
|

Is it True That the Normal Valence‐Length Correlation Is Irrelevant for Metal–Metal Bonds?

Abstract: The most intriguing feature of metal-metal bonds in inorganic compounds is an apparent lack of correlation between the bond order and the bond length. In this study, we combine a variety of literature data obtained by quantum chemistry and our results based on the empirical bond valence model (BVM), to confirm for the first time the existence of a normal exponential correlation between the effective bond order (EBO) and the length of the metal-metal bonds. The difference between the EBO and the formal bond ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…3, Co(1)-Pt(2) = 2.6359 (19), Co(2)-Pt(2) = 2.9791 (18), Co(3)-Pt(2) = 2.6322 (19), Co(4)-Pt(2) = 3.0428 (19), Co(2)-Pt(1) = 2.6389 (19), Co(3)-Pt(1) = 2.8972 (18), Co 4 3 The bond indices for the Co-Pt bonds can be divided into two sets, with values in the ranges 0.13-0.16 (Pt(1)-Co(1), Pt(1)-Co(3), Pt(2)-Co(4) and Pt(2)-Co(2)), and 0.21-0.24 (Pt(1)-Co(4), Pt(1)-Co(2), Pt(2)-Co(1) and Pt(2)-Co(2)). They correlate well with both the calculated and experimental bond lengths; those with shorter bond lengths correspond to higher bond indices, in accord with the trend reported for metal-metal bonds [12]. Although there are no reports of bond indices for Co-Pt bonds, it has been reported that homonuclear metal-metal bonds such as the single Ru-Ru bond has bond index ∼0.2 [13], and that for a single Fe-Fe bond has bond index ∼0.1 [14].…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…3, Co(1)-Pt(2) = 2.6359 (19), Co(2)-Pt(2) = 2.9791 (18), Co(3)-Pt(2) = 2.6322 (19), Co(4)-Pt(2) = 3.0428 (19), Co(2)-Pt(1) = 2.6389 (19), Co(3)-Pt(1) = 2.8972 (18), Co 4 3 The bond indices for the Co-Pt bonds can be divided into two sets, with values in the ranges 0.13-0.16 (Pt(1)-Co(1), Pt(1)-Co(3), Pt(2)-Co(4) and Pt(2)-Co(2)), and 0.21-0.24 (Pt(1)-Co(4), Pt(1)-Co(2), Pt(2)-Co(1) and Pt(2)-Co(2)). They correlate well with both the calculated and experimental bond lengths; those with shorter bond lengths correspond to higher bond indices, in accord with the trend reported for metal-metal bonds [12]. Although there are no reports of bond indices for Co-Pt bonds, it has been reported that homonuclear metal-metal bonds such as the single Ru-Ru bond has bond index ∼0.2 [13], and that for a single Fe-Fe bond has bond index ∼0.1 [14].…”
Section: Methodssupporting
confidence: 90%
“…The Co-C carbide and Co-Co bond lengths (1.846(12) -1.869(12) and 2.518(3) -2.705(3) Å, respectively) in 5 are comparable to those in the homometallic, octahedral cluster [Co 6 ( 6 -C)(CO) 13 ] 2-(1.852(3) -1.880 and 2.4618(8) -2.926(1) Å, respectively)[11]. The Pt-C carbide and the Co-Pt bond…”
mentioning
confidence: 99%
“…the effective number of shared electron pairs is very close to the formal one. As demonstrated below, the exception is the metal-metal bonds with a more complicated rule of local electroneutrality (Levi & Aurbach, 2011;Levi et al, 2013aLevi et al, ,b, 2014Singh et al, 2016).…”
Section: Analysis Of Quantum Chemistry Datamentioning
confidence: 99%
“…It was shown that the striking difference between formal and effective BOs of the TM-TM and TM-L bonds in cluster compounds is caused by a steric conflict between unusually short metal-metal bonds and a rigid ligand environment (Levi et al, 2013b;Singh et al, 2016). The conflict results in lattice strain, while the redistribution of the ED between the TM-TM and TM-L bonds ensures their partial or full relaxation.…”
Section: The Bo Analysis For a Series Of The Re 6 -Cluster Complexesmentioning
confidence: 99%
See 1 more Smart Citation